OPTIMALISASI PEMBUDAYAAN GERAKAN ANTI KORUPSI DALAM PENCEGAHAN KORUPSI DI PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA APARATUR - Zulkifli, Zulkifli (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2021)
ABSTRACTThe Anti-Corruption Movement is a movement that remains relevant to be promoted, especially since there are still many perpetrators who have been caught red-handed (OTT) by law enforcement officials (KPK). This study intends to reveal the relationship between two variables, namely the Culture of the Anti-Corruption Movement in Corruption Prevention and the locus in the PPSDM Aparatur. This study aims to determine the process of anti-corruption culture and the process of preventing corruption in the prevention of corruption in the PPSDM apparatus. This study uses a quantitative approach with an explanative method, the type of data is quantitative, the sample is determined based on the Slopin method with data collection techniques through a questionnaire, while the data analysis uses descriptive analysis, validity and reliability tests and correlation analysis. The hypothesis of this research is that the more optimal the culture of the anti-corruption movement is, the more effective the prevention of corruption is in the PPSDM Aparatur, which means that there is a positive relationship between the variables of the culture of the anti corruption movement and the variable of preventing corruption. ABSTRAKGerakan Anti Korupsi menjadi gerakan yang tetap relevan untuk digalakkan terlebih masih banyaknya pelaku yang tertangkap tangan (OTT) oleh aparat penegak hukum (KPK). Penelitian ini hendak mengungkap hubungan yang terjadi antara dua variable yaitu Pembudayaan Gerakan Anti Korupsi dalam Pencegahan Korupsi dengan lokus di PPSDM Aparatur. Penelitian ini bertujuan untuk mengetahui proses Pembudayaan Anti Korupsi dan proses pencegahan korupsi dalam Pencegahan Korupsi di PPSDM Aparatur. Penelitian ini menggunakan pendekatan kuantitatif dengan metode explanatif, jenis datanya kuantitatif, sampel ditentukan berdasarkan metode Slopin dengan teknik pengumpulan data melalui angket/kuesioner sedangkan analisis data dengan melakukan analisis dekriptif, uji validitas dan realibilitas serta analisis korelasi. Adapun hipotesis penelitian ini adalah semakin optimal pembudayaan gerakan anti korupsi maka semakin efektif pencegahan korupsi di PPSDM Aparatur yang berarti terdapat hubungan positif antara variabel pembudayaan gerakan anti korupsi dengan variabel pencegahan korupsi.